Mixed pain: has pain medicine overlooked Its most common phenotype for over 20 years? A perspective on mechanistic interaction, the nociplastic paradox, and the future of pain classification - Rainer Freynhagen; Antonio Alcántara Montero (Frontiers in Medicine, 2026)
Pain medicine has progressively evolved from a binary classification of nociceptive and neuropathic pain toward a broader mechanistic framework that now includes nociplastic pain. While this evolution has substantially improved our understanding of chronic pain, it has not resolved a persistent clinical reality: most patients do not present with mechanistically pure pain states. Instead, nociceptive, neuropathic, and nociplastic mechanisms frequently coexist within the same individual and interact in ways that challenge traditional classifications. The concept of mixed pain emerged more than two decades ago to capture this complexity. Despite growing recognition across conditions such as back pain, osteoarthritis, cancer pain, postsurgical pain, and fibromyalgia, mixed pain remains largely absent from formal pain taxonomy. At the same time, the increasing acceptance of nociplastic pain has revealed an important paradox. Current terminology explicitly acknowledges the coexistence of nociceptive and nociplastic mechanisms but provides no equivalent conceptual framework for neuropathic–nociplastic overlap, despite growing evidence that this combination is common and clinically relevant. Mixed pain should not be viewed as a diagnosis, a substitute for mechanistic assessment, or a label for pain of unknown origin. Rather, it requires the identification of at least two clinically relevant pain mechanisms contributing to the same clinical presentation. According to the recently accepted international consensus definition, mixed pain is pain associated with a lesion, disease, or disorder resulting in an overlap of at least two mechanistic descriptors (nociceptive, neuropathic, or nociplastic). Thus, mixed pain provides a framework for mechanistic integration rather than mechanistic replacement, helping to prevent its misuse as a diagnostic shortcut. Beyond simple coexistence, emerging evidence suggests that interaction between pain mechanisms may itself have biological and clinical significance. Mixed pain may influence symptom burden, treatment response, and prognosis in ways that cannot be fully explained by individual mechanisms alone. The next frontier in pain medicine may therefore not be the discovery of additional pain mechanisms, but a better understanding of how established mechanisms interact. Twenty years after the first challenge to mechanistic purity, the question is no longer whether pain mechanisms coexist. The question is whether we have underestimated the importance of their interaction.